2021
DOI: 10.3390/rs13183600
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Land Cover Classification with U-Net: Advantages of Combining Sentinel-1 and Sentinel-2 Imagery

Abstract: The U-net is nowadays among the most popular deep learning algorithms for land use/land cover (LULC) mapping; nevertheless, it has rarely been used with synthetic aperture radar (SAR) and multispectral (MS) imagery. On the other hand, the discrimination between plantations and forests in LULC maps has been emphasized, especially for tropical areas, due to their differences in biodiversity and ecosystem services provision. In this study, we trained a U-net using different imagery inputs from Sentinel-1 and Sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 89 publications
0
43
0
Order By: Relevance
“…Furthermore, our model can effectively distinguish economic forests from other land types, such as greenhouses, windbreaks, and vegetables, with validation and prediction accuracies of 0.91 and 0.90, respectively (Figure 6). U-net is among the most popular algorithms in land use/land cover (LULC) research, which combines several benchmark data sets to achieve state-of-the-art performance based on spectral and spatial information with limited training data [48,49]. Furthermore, our results indicated that pixel-based U-net might be suitable for precisely identifying economic forests and windbreaks, which warrants further large-scale research and validation.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, our model can effectively distinguish economic forests from other land types, such as greenhouses, windbreaks, and vegetables, with validation and prediction accuracies of 0.91 and 0.90, respectively (Figure 6). U-net is among the most popular algorithms in land use/land cover (LULC) research, which combines several benchmark data sets to achieve state-of-the-art performance based on spectral and spatial information with limited training data [48,49]. Furthermore, our results indicated that pixel-based U-net might be suitable for precisely identifying economic forests and windbreaks, which warrants further large-scale research and validation.…”
Section: Discussionmentioning
confidence: 79%
“…distinct land uses, be it limited and not always in an urban context (Solórzano et al, 2021;Giang et al, 2020;Zhang, Liu, and Wang, 2017). 4…”
Section: Methodsmentioning
confidence: 99%
“…However, in the literature, most of the land cover mapping papers still use single modality data [19][20][21]. Along with the technical developments in computational imaging and deep/machine learning research, the usage of multi-modal for land cover mapping data [22,23], despite being in early stages and insufficient, start to appear in some works in the recent years.…”
Section: Related Workmentioning
confidence: 99%